Wildlife Habitat Is Similar at Mined Versus Unmined Sites 30 Years Following Surface Mining for Coal in Southern Illinois. (April 2016) - Nielsen, Clayton K.; Kelly, Veronica L.
Abstract: Riparian ecosystems provide important habitat for wildlife and serve as corridors for animal movements. Surface mining activities clearly impact wildlife habitat by removing vegetation needed by wildlife. However, few studies have assessed longer‐term success of habitat restoration in riparian ecosystems following surface mining. During 2012–13, we evaluated microhabitat quality at three stream segments restored 30 years ago following surface mining for coal and one unmined stream segment in Perry County, Illinois. Microhabitat differences were very minor among restored and control stream sites. Of the 41 habitat variables measured, 14 differed among sites, four of which were uncorrelated: canopy cover, overstory hard mast, bare ground, and herbaceous ground cover; thus, restored riparian buffers were comparable to unmined sites, indicating that habitat restoration efforts were successful. Our analysis from data collected at Burning Star 4 mine in Perry County, Illinois, is of value to land managers for it shows how the reclamation process has successfully jump‐started wildlife habitat in buffers around streams affected by mining.